2016
DOI: 10.1111/rda.12750
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the uniparous and multiparous goats ovaries

Abstract: Transcriptome analysis of Inner Mongolia Cashmere goat and Dazu black goat generated 38,772,947 and 38,771,668 clean pair end reads, respectively, which were assembled into 72,422 and 80,069 unigenes by Trinity, respectively. For Inner Mongolia Cashmere goat, 26,051 and 10,100 unigenes were assigned to gene ontology (GO) categories and clusters of orthologous groups, respectively. A total of 32,772 unigenes can comment to SWISS-Prot database, and the Kyoto Encyclopedia of Genes and Genomes Pathway database (KE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Among them, cell parts and cells, binding and catalytic activity, metabolic processes, and cellular processes were predominant in each of the three main categories, respectively. These observations are consistent with previous studies regarding ovarian transcriptomes of goats (Ling et al, 2014;Miao et al, 2016;Wang et al, 2016;Zhao et al, 2015) and pigs . Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway significant enrichment analysis revealed that the DEGs participated in 331 pathways, of which 22 significantly enriched pathways were identified in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Among them, cell parts and cells, binding and catalytic activity, metabolic processes, and cellular processes were predominant in each of the three main categories, respectively. These observations are consistent with previous studies regarding ovarian transcriptomes of goats (Ling et al, 2014;Miao et al, 2016;Wang et al, 2016;Zhao et al, 2015) and pigs . Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway significant enrichment analysis revealed that the DEGs participated in 331 pathways, of which 22 significantly enriched pathways were identified in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…On average, a total of 15,719 and 15,738 genes were expressed in each TBG and JTG ovary, respectively. Previous transcriptome studies of ovaries used samples from multiple pooled ovary RNA for analysis (Ling et al., ; Miao et al., ; Wang et al., ; Zhao et al., ). Pooling methods would possibly mask individual ovary variability and gene expression heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations